A toolbox facilitating stable transfection of Eimeria species - Clark, Julie D.; Billington, Karen; Bumstead, Janene M.; Oakes, Richard D.; Soon, Puay Eng; Sopp, Paul; Tomley, Fiona M.; Blake, Damer P. (Molecular and biochemical parasitology, 2008)
Stable transfection of Eimeria species has been difficult to achieve because of the obligate requirement for in vivo amplification and selection of the parasites. Strategies to generate and stabilise populations of transfected Eimeria tenella are described here, together with the identification of optimal parameters for the transfection process. A series of plasmids expressing selectable markers, including a panel of fluorescent reporter genes and a mutant Toxoplasma gondii dihydrofolate reductase–thymidylate synthase (DHFR-TSm2m3) gene that confers resistance to pyrimethamine, were electroporated into sporozoites of the E. tenella Wisconsin strain and stabilised by selective passage through chickens. Very high transfection efficiencies of up to 25% sporozoites in transient transfection and up to 9% oocysts following a single round of in vivo selection were achieved. Crucial factors include the use of very freshly harvested parasites with the AMAXA nucleofection system (program U33 in a cytomix-buffered reaction) and linearised plasmid DNA. The use of a restriction enzyme mediated integration (REMI) protocol boosted overall efficiency and elevated insertion rate per genome. Successful development of methods to generate and isolate stable populations of transfected Eimeria parasites will now stimulate rapid expansion of reverse genetic studies in this important coccidian.